Presynaptic G-Protein-Coupled Receptors Regulate Synaptic Cleft Glutamate via Transient Vesicle Fusion - Schwartz, Eric J. (J Neurosci, 2007)
When synaptic vesicles fuse with the plasma membrane, they may completely collapse or fuse transiently. Transiently fusing vesicles remain structurally intact and therefore have been proposed to represent a form of rapid vesicle recycling. However, the impact of a transient synaptic vesicle fusion event on neurotransmitter release, and therefore on synaptic transmission, has yet to be determined. Recently, the molecular mechanism by which a serotonergic presynaptic G-protein-coupled receptor (GPCR) regulates synaptic vesicle fusion and inhibits synaptic transmission was identified. By making paired electrophysiological recordings in the presence and absence of low-affinity antagonists, we now demonstrate that activation of this presynaptic GPCR lowers the peak synaptic cleft glutamate concentration independently of the probability of vesicle fusion. Furthermore, this change in cleft glutamate concentration differentially inhibits synaptic NMDA and AMPA receptor-mediated currents. We conclude that a presynaptic GPCR regulates the profile of glutamate in the synaptic cleft through altering the mechanism of vesicle fusion leading to qualitative as well as quantitative changes in neural signaling.